Oral Loading of Phenobarbital to Achieve Therapeutic Effects in Pediatric Patients with Acute Repetitive Seizures - Jemima Grace D. Fronda; Mel Michel G. Villaluz; Cristina M. Cruz-Urbi (Korean Child Neurology Society, 2023)
Purpose Intravenous phenobarbital has not been available at our institution since 2019. This study aimed to determine the effectiveness of oral phenobarbital loading at a dose of 15 to 20 mg/kg to achieve therapeutic serum levels and clinical seizure control in pediatric patients with acute repetitive seizures. Methods This is a retrospective single-center review of the medical records of pediatric patients admitted for acute repetitive seizures (from January 2019 to June 2022) at the Philippine Children's Medical Center who were given an oral phenobarbital loading dose of 15 to 20 mg/kg with serum level measurements taken within 48 hours after oral loading. Results Eleven patients were given a single oral phenobarbital loading dose of 15 to 20 mg/kg, while 14 were given two doses of 10 mg/kg 12 hours apart. All 25 patients achieved therapeutic serum levels within 48 hours post-loading. Higher serum levels were seen at 48 hours (median, 19.8 μg/mL at 24 hours vs. 24.4 μg/mL at 48 hours). This difference was statistically significant at 5% (P=0.023), and the majority achieved adequate seizure control without requiring additional anti-seizure medications (76%). Transient drowsiness was the most commonly documented adverse effect. Conclusion Oral loading of phenobarbital at a dose of 15 to 20 mg/kg given as a single dose or in two divided doses is an effective and safe alternative to achieve therapeutic serum levels and adequate clinical seizure control at 24 hours post-loading. This may be a promising and useful intervention at centers without available intravenous phenobarbital.